2019
DOI: 10.1002/pd.5521
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic description of patients with prenatally identified cardiac tumors

Abstract: Objective: Rhabdomyomas are the most common type of prenatal cardiac tumors.When isolated, 50% to 70% are related to the tuberous sclerosis complex (TSC). The aim of this study was to reinforce the importance of additional clinical data in patients with prenatal heart tumors.Methods: From 2010 to 2017, 10 prenatally detected cardiac tumors were referred to the Genetics Department, and a complete family history was taken. Postnatal echocardiographic and full clinical evaluation were completed. Next generation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
1
7
0
4
Order By: Relevance
“…Rhabdomyomas are the most common type of prenatal cardiac tumors, when isolated, 50% to 70% are related to the tuberous sclerosis complex (TSC). 26 A recent study on 10 prenatally detected cardiac tumors, which were postnatally confirmed as rhabdomyomas, revealed three TSC2 mutations in four patients by NGS. 26 Together with our data, it is important to take consideration of conventional mutation screening in TSC2 gene for prenatal identified cardiac rhabdomyoma.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Rhabdomyomas are the most common type of prenatal cardiac tumors, when isolated, 50% to 70% are related to the tuberous sclerosis complex (TSC). 26 A recent study on 10 prenatally detected cardiac tumors, which were postnatally confirmed as rhabdomyomas, revealed three TSC2 mutations in four patients by NGS. 26 Together with our data, it is important to take consideration of conventional mutation screening in TSC2 gene for prenatal identified cardiac rhabdomyoma.…”
Section: Discussionmentioning
confidence: 97%
“…Clinical data of the study cohort Age of pregnant women (median) y (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41) Gestational weeks (median) wk Sex of fetuses (M/ Data analysis and filtering were documented detailed in our previous publications. 12 The raw image files were processed using bcl2fastq software (Illumina) for base calling and raw data generation.…”
Section: T a B L Ementioning
confidence: 99%
“…The first detected alteration in TSC fetus is cardiac rhabdomyoma, a benign fetal cardiac tumor commonly associated with TSC (Bader et al, 2003;Saada et al, 2009), and this was the case for the majority of the cases investigated here. With the development of high-resolution ultrasound echocardiography and magnetic resonance, the prenatal diagnosis in the second and third trimesters of pregnancy increased considerably (Bejiqi et al, 2017;Mariscal-Mendizábal et al, 2019). Prenatal diagnosis has gained interest with recent data suggesting that maternal treatment with inhibitors of the mTOR pathway (everolimus and sirolimus) may be beneficial for rhabdomyomas without any serious adverse events reported (Barnes et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies on TSC have been implemented in populations of Europe, USA, Canada and Brazil; hence, it is relevant to include more cases from other Latin American countries in order to investigate and expand the responsible TSC genotype, better delineate the clinical features and contribute to possibly identifying genotype-phenotype correlations. To our knowledge, there are only two previous published molecular studies of TSC patients in Mexico: one involving three patients with early-stage polycystic kidney disease that were molecularly confirmed to represent TSC2/PKD1 contiguous gene syndrome cases 17 and one involving three TSC2-cases with prenatally documented cardiac rhabdomyomas 18 . Therefore, in order to improve our knowledge of this disease and to spread the use of innovative and highly sensitive molecular techniques such as MLPA and NGS for the diagnosis of TSC in countries where the disease has been under-studied, we used a combined molecular strategy to analyze the mutational spectrum of TSC1 and TSC2 and the principal clinical features of 66 Mexican-descent unrelated cases of TSC.…”
mentioning
confidence: 99%